Entre Écriture Romanesque et Critique Cinématographique : Repenser le Cinéma dans la Littérature Contemporaine - Jean Cléder (Carnets)
Using cinematic material as a substrate or referent, contemporary writers have devised new modes of storytelling — drawing on pre-existing images — and of shaping destinies, which, in turn, offer a critical perspective on cinematic fictions. This study explores such forms of generic and media hybridisation, engaging with both experimental modes of writing and more mainstream narratives — in particular, biographical fictions that incorporate cinematic figures and, more broadly, what I term the « cinemato-graphy » of literary writing. My working hypothesis is the following : these emerging forms of writing displace cinema — its history and its narratives — from the purview of traditional film criticism, reconfiguring them through narrative rewritings that resonate profoundly with the current epistemological shift.